Kassab, Fatima. “Contemporary Perspectives on Muslim Classification of Various Regions of the World: A Literature Review,” Year 12, Issue 45 (Summer 1427 AH/ 2006 CE), Pp. 153-186. - كساب, فاطمة (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2006)
Fatima Kassab’s article highlights the main works in contemporary literature, including those in the field of political science, that address the Muslim classification of various regions or territories of the world. Kassab introduces the discourse on Muslim classification of regions, the relationship of Muslims with others in contemporary Muslim thought, and the ways in which Muslims are linked with others. She discusses in particular: the notion that war is the standard in the relationship between Muslims and others; the notion that peace is the standard in the relationship between Muslims and others—with daʿwah (Muslim outreach) being the basis that governs this relationship; and the literature in political science highlighting the importance of dār al-ʿahd (the abode of covenant or conciliation). Lastly, she addresses the legitimacy of the classification of world regions.